2015
DOI: 10.1111/his.12755
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and immunohistological features of polypoid endometriosis

Abstract: There are two main subgroups of PE. The majority of cases in this series showed similar histological features to NPE, but involved anatomical sites that facilitated exophytic or polypoid growth. The remaining PE cases resembled eutopic endometrial polyps histologically and immunophenotypically and they occurred in older patients. These findings suggest that such lesions are 'true' polyps sharing a pathogenetic relationship with similar lesions arising in the endometrium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
(42 reference statements)
0
15
0
Order By: Relevance
“…Ectopic endometrial glands resembling endometrial hyperplasia were found in one of the three cases in our hospital. Although Stewart and Bharat reported no malignant findings in the 15 cases, 40 our literature review indicated that the histological findings included endometrial hyperplasia without atypia in 15 cases, simple hyperplasia with atypia in four, and well‐differentiated endometrioid carcinoma in three (Table S1). The preoperative histological findings resemble endometrial hyperplasia making it difficult to differentiate PE from endometrial hyperplasia and endometrial cancer.…”
Section: Literature Review and Discussionmentioning
confidence: 73%
“…Ectopic endometrial glands resembling endometrial hyperplasia were found in one of the three cases in our hospital. Although Stewart and Bharat reported no malignant findings in the 15 cases, 40 our literature review indicated that the histological findings included endometrial hyperplasia without atypia in 15 cases, simple hyperplasia with atypia in four, and well‐differentiated endometrioid carcinoma in three (Table S1). The preoperative histological findings resemble endometrial hyperplasia making it difficult to differentiate PE from endometrial hyperplasia and endometrial cancer.…”
Section: Literature Review and Discussionmentioning
confidence: 73%
“…Gunawardane DN reported a 50-year-old female had a hysterectomy and bilateral salpingo-oophorectomy for adenomyosis, uterine leiomyomas, ovarian and cervical endometriosis. Nine months later, a mass between the vagina and rectum was diagnosed the Pouch of Douglas PEM [22] .But all of the 7 patients in our group were women of childbearing age, aged from 31 to 45 (38.00±1.72) years old. No such lesions were found in postmenopausal women, which may be due to the small sample size of the cases in this group or the difference in race.…”
Section: Other Cases Reported These Yearsmentioning
confidence: 75%
“…The surface is erosive or covered with a single layer of columnar, cubic, or dwarf cubic epithelium. It may be accompanied by a small amount of active epithelial hyperplasia, cystic dilatation of the gland, intensive hyperplasia of the focal glands, abundant interstitial cells in some parts, moderate atypia, nuclear mitosis, or borderline changes, metaplasia of the fallopian tube, and atypical hyperplasia, which also bring great confusion for pathological examination [22][23][24] . At present, the immunohistochemical studies on PEM mostly suggest ER(+), PR(+), and Vinmentin(++), as previously mentioned [26,29] .…”
Section: Clinicopathological Featuresmentioning
confidence: 99%
“…3 Polypoid endometriosis may typically affect peri-or postmenopausal women, and hormonal factors such as tamoxifen treatment can play a role in its pathogenesis. 2,3 Actually, nearly 50% of the patients with polypoid endometriosis were on hormonal treatment at the time of diagnosis. 4 Because polypoid endometriosis may form multiple polypoid nodules in the peritoneal cavity or endometriotic cysts mimicking malignant tumors on imaging examination, at surgery, and on gross pathologic examination, preoperative diagnosis on magnetic resonance (MR) imaging is important to avoid aggressive treatment.…”
Section: Introductionmentioning
confidence: 99%
“…4 Because polypoid endometriosis may form multiple polypoid nodules in the peritoneal cavity or endometriotic cysts mimicking malignant tumors on imaging examination, at surgery, and on gross pathologic examination, preoperative diagnosis on magnetic resonance (MR) imaging is important to avoid aggressive treatment. [1][2][3] The literature on polypoid endometriosis focusing on MR imaging findings is limited to case reports. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Several MRI findings have been reported to be useful in the diagnosis of polypoid endometriosis.…”
Section: Introductionmentioning
confidence: 99%